1999
DOI: 10.1046/j.1432-1327.1999.00570.x
|View full text |Cite
|
Sign up to set email alerts
|

The carbohydrates of the isoforms of three avian riboflavin‐binding proteins

Abstract: The carbohydrate chains of nine isoforms of chicken egg-white riboflavin-binding protein (RfBP) and six isoforms each of quail egg-white and yolk RfBP have been structurally characterized. The two N-glycosylation sites, Asn36 and Asn147, of the most abundant isoform of each of the three proteins were analyzed in further detail leading to the identification of different glycosylation patterns. In both chicken and quail egg-white RfBP the carbohydrates attached to position 36 had a lower degree of branching and,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…In the present study, spot 3 representing RFBP showed a slightly higher MW than theoretical value (Table. ), indicating possible glycosylation or a complex with riboflavin (Amoresano et al, ; Geng et al, ). The abundance of this protein was decreased significantly and almost disappeared after day 14 of incubation (Figures and ), suggesting a complete degradation or being absorbed integrally by the embryo during embryogenesis.…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, spot 3 representing RFBP showed a slightly higher MW than theoretical value (Table. ), indicating possible glycosylation or a complex with riboflavin (Amoresano et al, ; Geng et al, ). The abundance of this protein was decreased significantly and almost disappeared after day 14 of incubation (Figures and ), suggesting a complete degradation or being absorbed integrally by the embryo during embryogenesis.…”
Section: Resultsmentioning
confidence: 99%
“…Their different sources (e.g. chicken egg white, quail egg white, or yolk) showed various glycosylation patterns as well as diverse tertiary structures [34,35] , indicating their distinct biological functions during embryonic development.…”
Section: Resultsmentioning
confidence: 99%
“…20,21 In RfBP, the N-linked carbohydrates are found on residues Asn 36 and 147. 22 These positions are not included in the immunoreactive peptide 41−84. Therefore, IgE binds the peptide chain, rather than the carbohydrate moieties, suggesting that a potential IgE cross-reactivity of RfBP and ovomucoid would not be likely related to their carbohydrate moieties.…”
Section: ■ Results and Discussionmentioning
confidence: 99%